Aiming for Sustainability and Scalability: Community Engagement in Forest Payment Schemes - Kowler, L.F.; Pratihast, A.K.; Pérez Ojeda del Arco, A.; Larson, A.M.; Braun, C.; Herold, M. (MDPI, 2020)
Community-based forest monitoring is seen as a way both to improve community engagement and participation in national environmental payment schemes and climate mitigation priorities and to implement reducing emissions from deforestation and forest degradation and foster conservation, sustainable management of forests and enhancement of forest carbon stocks in developing countries (REDD+). There is a strong assumption among community-based monitoring advocates that community monitoring is a desirable approach. However, it is unclear why community members would want to participate in their own surveillance or be involved in a program likely to limit livelihood uses of forest areas and possibly even sanction them based on the data provided. This paper explores these issues by examining three communities involved in Peru’s Conditional Direct Transfer Program, in which indigenous communities are compensated for protecting communal forests through various mechanisms, including forest monitoring. The case studies focus specifically on communities that received smartphones and were trained in their use for monitoring. The results affirm the importance that benefits outweigh the costs of local participation to sustain motivation. They also point to key factors supporting the legitimacy of the program, specifically to overcome historical tensions between the state and indigenous communities. These include the nature of engagement by program implementers and the importance of building trust over time.